Co‐design of the EMBED‐Care Framework as an intervention to enhance shared decision‐making for people affected by dementia and practitioners, comprising holistic assessment, linked with clinical decision support tools: A qualitative study - Jesutofunmi Aworinde; Catherine J. Evans; Juliet Gillam; Christina Ramsenthaler; Nathan Davies; Clare Ellis‐Smith; EMBED‐Care Programme (Wiley, 2024)
Abstract Introduction Shared decision‐making intends to align care provision with individuals' preferences. However, the involvement of people living with dementia in decision‐making about their care varies. We aimed to co‐design the EMBED‐Care Framework, to enhance shared decision‐making between people affected by dementia and practitioners. Methods A theory and evidence driven co‐design study was conducted, using iterative workshops, informed by a theoretical model of shared decision‐making and the EMBED‐Care Framework (the intervention) for person‐centred holistic palliative dementia care. The intervention incorporates a holistic outcome measure for assessment and review, linked with clinical decision‐support tools to support shared decision‐making. We drew on the Medical Research Council (MRC) guidance for developing and evaluating complex interventions. Participants included people with dementia of any type, current or bereaved family carers and practitioners. We recruited via established dementia groups and research and clinical networks. Data were analysed using reflexive thematic analysis to explore how and when the intervention could enhance communication and shared decision‐making, and the requirements for use, presented as a logic model. Results Five co‐design workshops were undertaken with participants comprising people affected by dementia (n = 18) and practitioners (n = 36). Three themes were generated, comprising: (1) 'knowing the person and personalisation of care', involving the person with dementia and/or family carer identifying the needs of the person using a holistic assessment. (2) 'engaging and considering the perspectives of all involved in decision‐making' required listening to the person and the family to understand their priorities, and to manage multiple preferences. (3) 'Training and support activities' to use the Framework through use of animated videos to convey information, such as to understand the outcome measure used to assess symptoms. Conclusions The intervention developed sought to enhance shared decision‐making with individuals affected by dementia and practitioners, through increased shared knowledge of individual priorities and choices for care and treatment. The workshops generated understanding to manage disagreements in determining priorities. Practitioners require face‐to‐face training on the intervention, and on communication to manage sensitive conversations about symptoms, care and treatment with individuals and their family. The findings informed the construction of a logic model to illustrate how the intervention is intended to work.